2019
DOI: 10.7717/peerj.6438
|View full text |Cite
|
Sign up to set email alerts
|

The association between meteorological variables and road traffic injuries: a study from Macao

Abstract: ObjectiveCorrelation analysis and multiple linear regression analysis were conducted to estimate the influence of meteorological factors on road traffic injuries stratified by severity. Crash rate was defined as mean monthly road traffic accidents per 1,000 vectors.DesignEcological time-series study.SettingMacao traffic accident registry database between January 1st, 2001 and November 31st, 2016.ParticipantsIn total, 393,176 traffic accidents and 72,501 cases of road traffic injuries (RTIs) were enrolled; pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In the table (7) we have presented the training results of YOLOv3 and TINYv3 detectors of the modified SCUT dataset. We have used two thresholds for IoU, which were set to 50% and 25%.…”
Section: Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the table (7) we have presented the training results of YOLOv3 and TINYv3 detectors of the modified SCUT dataset. We have used two thresholds for IoU, which were set to 50% and 25%.…”
Section: Validationmentioning
confidence: 99%
“…One of the causes of traffic accidents is the bad weather condition. Rain, fog, snow, and wind are factors affecting visibility and act via a psycho-physiological function of the driver [5], [6], increasing the traffic accident rate by up to 13% [7], [8]. The leading countries in traffic safety are the United Kingdom, Denmark, and Ireland.…”
Section: Introductionmentioning
confidence: 99%
“…Children and adolescents are prone to outdoor environmental factors due to their increased independence and elevated activity levels (Patton et al, 2016). Ambient temperature changes may affect human behavioral patterns and traffic intensity (Abe et al, 2008;Gao et al, 2016;Lio et al, 2019). For instance, an optimal ambient temperature may lead to increased outdoor activities among children and adolescents, resulting in a rising incidence of unintentional injuries.…”
Section: Introductionmentioning
confidence: 99%
“…A global analysis reported that the deaths due to road crashes attributable to high temperatures significantly increased from 20,270 in 1990 to 28,396 in 2019 [14]. A growing body of evidence has shown that high ambient temperatures are associated with an increased risk of road traffic crashes [15][16][17][18][19][20]. For example, a study in China reported that significantly more road crashes occurred during summer [17].…”
Section: Introductionmentioning
confidence: 99%